Economic efficiency of the opened ground vegetables production at the agricultural enterprises in Cherkasy region - Андрусяк, Н. О. (Scientific Progress & Innovations, 2012)
In the article is analyzed the economic efficiency of opened ground vegetables production in Cherkasy region. Using the general statistical report the analysis of main economic indicators of open ground vegetable production was considered. Territory difference in opened ground vegetables production with using integral efficiency index was determined. Factors which show the results of activity and found the ways of improvement economic efficiency of vegetables production was also.